Analysis of Evolution of the Wetland Ecosystem of the Liaohe River Nature Reserve over the Past 40 Years and Its Driving Factors - SUN Xiangru; CHEN Jiabo; WANG Yanjie (Renmin Zhujiang)
The wetland in the Liaohe River Nature Reserve has played a crucial role in pollutant purification and biodiversity protection for the Liaohe River Basin.This paper reviews the evolution of the wetland ecosystem of the Liaohe River Nature Reserve over the past 40 years and analyzes the major factors driving the process,and puts forward measures for wetland conservation and prospects for future research.The results show that:From 1980 to 2010,the total wetland area showed a decrease trend.Except for the protected area at the estuary of the Liaohe River,the Liaohe River Nature Reserve suffered scarce plant resources and extremely low diversity of plant species,making it unsuitable to serve as a breeding habitat for most birds and fishes.From 2010 to 2020,with the rapid recovery in wetland area,the macro plant structure and diversity improved significantly,resulting in a substantial increase in bird and fish populations.Major natural factors driving the changes of wetland include temperature and precipitation,while human factors such as agricultural development,water project construction,oil and gas exploration,urbanization,and exotic species invasion play a central role in the process.Currently,key measures such as strictly guaranteeing ecological water demand,re-planting aquatic vegetation in land-water cross bedding and open water areas,and conducting integrated control of exotic species invasion through physico-chemical and ecological prevention measures should be taken to promote wetland conservation.The future research should focus on wetland developmental mechanism of the Liaohe River Nature Reserve based on the basin scale.